Mapping of Difficult Mathematics Topics in Vocational High Schools Based on National Examination Data - Retnawati, Heri; Arliani, Elly; Apino, Ezi; Djidu, Hasan; Kartianom, NFN; Santoso, Agus; Rasmuin, NFN (Indonesian Journal of Educational Assessment, 2020)
The educational achievement in Indonesia is measured by implementing the National Examination or Ujian Nasional (UN). Throughout its implementation, the UN results shown unsatisfying results, including in mathematics subjects. This fact indicated that there are mathematics topics that are considered to be difficult for students. This study aimed to investigate the difficult topics of mathematics in Vocational High School (VHS) based on UN data. This study was a descriptive research with the quantitative approach by using the UN report results in the level of VHS from Center for Educational Assessment of the Ministry of Education and Culture in the period of 2008 to 2017 (ten years) as a research data source. Data analysis was carried out in a quantitative descriptive by mapping the mathematics topics based on proportion correct answers or â€œdaya serapâ€. A topic was considered difficult if the proportion correct answer was less than 50%. The results showed that there were 14 difficult mathematics topics in the UN implementation at the VHS level from 2008 to 2017. These topics include the comparison of trigonometric functions, solid figure, limit, measure of data dispersion, permutation and combination, differential, area between two curves, a measure of central data tendentious, probability, logarithm, integral, sequence and series, linear program, and polar coordinates system. The implications of the research findings for learning practice and future research opportunities are discussed.